Health Policy in Bogota (2004-2008):An Analysis of the Experience with Primary Health Care - Roman Vega Romero; Naydu Acosta Ramirez; Paola Andrea Mosquera Mendez; Maria Ofelia Restrepo Velez (Social Medicine Publication Group, 2008)
This study summarizes the health policy and the Primary Health Care strategies developed by the Bogota municipal government from 2004-2008. The experiences and outcomes during this time period indicate that, despite the market-oriented health policy that exists in Colombia, it was beneficial to implement health policies and strategies at the local level so as to guarantee the right to health and equitable access to health care. National level restrictions, however, impose constraints on the potential implementation of such policies and strategies. This suggests that in order to achieve effective and sustainable changes at the local level, it is necessary to promote substantial reforms within national health care policy.